2011
DOI: 10.5539/ijbm.v6n5p268
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Infrastructure on Foreign Direct Investment: The Case of Pakistan

Abstract: Purpose -The purpose of this study is to analyze the role of infrastructure for and in ascertaining captivations of foreign direct investment (FDI). This work aims to investigate the effects of host country's infrastructure availability along with exchange rate and market size on inflows of FDI towards Pakistan.Design/methodology/approach -This study employs autoregressive distributed lag (ARDL) approach to cointegration and an error correction model based on ARDL approach using time series data for the period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 37 publications
4
24
2
3
Order By: Relevance
“…In economies like Pakistan where, though less of export oriented, plenty of established firms exist in different race of business, new investors are found as feeling less satisfied if cost of borrowing capital as well as exchange rates are volatile in respect of upward movement. Therefore, our results are well justified in publishing that interest rate and exchange rate both, as found earlier by Zaman et al (2012), effect FDI inflows in inverse, unlike Rehman et al (2011) and Mehmood and Faridi (2013), on account of exchange rate, for exclusive. Investment theory of firm described factors like of bad governance, uncertain law and order that uncertain the future profit expectation.…”
Section: Long-run Coefficientssupporting
confidence: 86%
See 1 more Smart Citation
“…In economies like Pakistan where, though less of export oriented, plenty of established firms exist in different race of business, new investors are found as feeling less satisfied if cost of borrowing capital as well as exchange rates are volatile in respect of upward movement. Therefore, our results are well justified in publishing that interest rate and exchange rate both, as found earlier by Zaman et al (2012), effect FDI inflows in inverse, unlike Rehman et al (2011) and Mehmood and Faridi (2013), on account of exchange rate, for exclusive. Investment theory of firm described factors like of bad governance, uncertain law and order that uncertain the future profit expectation.…”
Section: Long-run Coefficientssupporting
confidence: 86%
“…In capturing the data from 1975 to 2008 in line with the ARDL, the study conducted by Rehman, Ilyas, Mobeen and Akram (2011) found that real exchange rate, market size and the local infrastructure (in terms of the importation of machinery) brought positive and significant effect on the flow of FDI to Pakistan. Same results on accord of Johansen Juselius (1990) technique and ECM were depicted by Abbas, Akbar, Nasir, Ullah and Naeem (2011).…”
Section: The Determinants Of Fdimentioning
confidence: 99%
“…A study by Hakro and Omezzine (2011) to study the link between FDI flows and governance infrastructure in Mena Region countries found that governance infrastructure has a significant positive impact on FDI flows to the regions. Rehman et al (2011) studied the impact of infrastructure on FDI in Pakistan over the period 1975-2008 and found that infrastructure and market size were positively related and exchange rate negatively related to FDI inflows in the short-run and in the long-run. Asiedu (2002) investigated the determinants of FDI in 70 developing countries, 35 of which are from the Sub-Saharan Africa region, for the period between 1988 and 1997 infrastructural development and economic openness were key to attracting FDI.…”
Section: Infrastructurementioning
confidence: 99%
“…The empirical study carried out by Rehman et al (2011) on the impact of infrastructure on FDI in Pakistan over the period between 1975 and 2008. The study examined the roles infrastructure play in attracting FDI and investigated the effects of exchange rate, market size and availability of infrastructure on FDI inflow to Pakistan.…”
Section: Literature Reviewmentioning
confidence: 99%